Student Teachers’ Perspectives on Academic Support Services in Open and Distance Learning - Fareed Mohamed, Nawastheen; K.S., Pavani Sisindra; N.G.L.S.J. , Liyanage; Fernando, Ann Purnima Sandamini; R.S., Dilakshan (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Academic support services are crucial for student success in open and distance learning (ODL), particularly in teacher education where learners balance multiple responsibilities. This study examined student teachers’ perspectives on academic support within the Bachelor of Education (B.Ed.) and Postgraduate Diploma in Education (PGDE) programmes at the Open University of Sri Lanka. Grounded in Tait’s (2000) tripartite framework and Keller’s (1987, 2009) ARCS Model, it assessed support effectiveness and identified enhancement areas. A survey was administered to 474 student teachers examining six dimensions: academic counselling, interactive learning sessions, assessment feedback, self-learning materials, mentoring during teaching practice, and online learning support. Descriptive statistics and inferential analyses (t-tests and ANOVA) examined perceptions and variations across gender, programme type, and study centres. Findings revealed generally positive perceptions, with mentoring and teaching practice receiving highest satisfaction (M = 3.77, SD = 0.65), followed by interactive learning sessions (M = 3.73, SD = 0.65). Notable gaps emerged in self-learning materials (M = 3.43, SD = 0.73), online learning support (M = 3.45, SD = 0.73), and assessment feedback (M = 3.46, SD = 0.65). Gender analysis showed significant differences only in assignment feedback perceptions, with males reporting higher satisfaction (p = .007). No significant differences existed between B.Ed. and PGDE students, suggesting equitable programme support. However, significant variations across study centres were identified for all dimensions (p < .05), highlighting service quality disparities. Recommendations include enhancing counselling accessibility, standardizing mentoring structures, improving self-learning materials, and strengthening online infrastructure for equitable support in teacher education programmes.